OPTIMAL INVESTMENT DECISION USING NEURAL REDUCT FUZZY SET OF IVFS - Muthumeenakshi, M.; Muralikrishna, P. (Italian Journal of Pure and Applied Mathematics, 2015)
Taking optimal investment decision is very challenging in the current scenario. Traditionally, the investors were followed fundamental analysis or technical analysis in the investment decision. But, today the market and technology are growing very faster than the investors’ ideas. Every new method is coming for the investment analysis. All the decisions are future oriented which relies uncertainty. It is inevitable to apply a tool which is linked with the uncertainty. Hence, in this study, ’IVFS’ technique has been used which measures the uncertainty. Finding out the exact membership in Interval Valued Fuzzy is a crucial part in the investment analysis. To reduce this problem, here the notion of neural reduct fuzzy set of interval valued fuzzy set has been applied. In a clear sense, this paper finds the membership using interval value and converge into one single point that act as member for the fuzzy set.